In Vitro Evaluation of Alpha-Amylase Inhibitory Activity of Ethanolic Leaf Extracts of Aegle marmelos and Turnera ulmifolia - Satyasuma, Sunkara; Yanagala, Swathi; Vipparthi, Kavya Sri; Yamala, Sai Meghana; Yalla, Jyothi Vijaya Sai; Veliventi, Siva Kalyani; Grandhi, Abhinav VKS; Devanaboyina, Narendra (International Journal of Life Science and Pharma Research, 2025)
Aegle marmelos (Bael), a medicinal plant widely used in traditional Ayurvedic medicine, has shown promising antidiabetic, antioxidant, and hepatoprotective effects. Their leaves contain many bioactive constituents such as flavonoids, tannins, alkaloids, and coumarins, contributing to their therapeutic potential. Similarly, Turnera ulmifolia, commonly known as yellow alder, is an ethnomedicinal plant exhibiting antihyperglycemic, antioxidant, and anti-inflammatory activities. This study investigates the in vitro α-amylase inhibitory potential of ethanolic leaf extracts of Aegle marmelos and Turnera ulmifolia. The extracts were prepared by cold maceration and assessed using the DNS assay. Among the tested samples, Aegle marmelos demonstrated notable inhibitory activity, while Turnera ulmifolia showed minimal effect. These findings support the traditional use of Aegle marmelos in diabetes management and highlight the need for further studies to isolate active constituents and evaluate their in vivo efficacy.